Imaging of surface atoms revolving on elliptical trajectories - Hesjedal, T; Chilla, E; Frohlich, H (1998)
Achieving atomic resolution with an STM demands a noise-free environment, where mechanical vibrations especially must be damped out. Introducing such vibrations in the form of defined ultrasound consequently leads to image distortion. In particular, the topography is smeared out. By employing surface acoustic waves, which lead to an oscillation of surface atoms on elliptically polarized trajectories, this smearing-out is directed, thereby giving a projection of the ellipse on the sample plane. However, by employing a stroboscopic heterodyne technique (mixing the highfrequency tunneling current with a slightly detuned electrical signal which is applied across the tunneling gap) a snapshot of the surface oscillation is seen.We present phase and amplitude images exhibiting atomic resolution. The atomic contrast of phase and amplitude is explained by the superposition of the surface topography and the oscillation trajectory, which can be obtained from a continuum theory model. © 1998 Springer-Verlag.